Exploring religious motivation as a moderator of word-of-mouth in Islamic banking - Hukama, La Diadhan; Setianingrum, Any; Zain, Efendy; Simon, Zainal Zawir; Ghazali, Muh. (Asian Journal of Islamic Management (AJIM), 2026)
Purpose – This study examines the effects of service quality, service convenience, religious motivation, and customer satisfaction on word-of-mouth (WOM) behavior in Indonesian Islamic banking. It also investigates whether religious motivation moderates the relationship between customer satisfaction and WOM.Methodology – A quantitative approach was employed using purposive sampling of Islamic bank customers who had maintained an active account for at least one year. Data were collected from 195 respondents and analyzed using WarpPLS 6.0 to assess the measurement and structural models and test the proposed hypotheses.Findings – The results demonstrate that service quality and service convenience significantly enhance customer satisfaction. Furthermore, service quality, religious motivation, and customer satisfaction have significant positive effects on WOM behavior. However, service convenience does not directly influence WOM, and religious motivation does not moderate the relationship between customer satisfaction and WOM. These findings indicate that customer satisfaction is the primary driver of customers’ willingness to recommend Islamic banks, regardless of their level of religious motivation.Implications – Islamic banks should prioritize improving service quality and sustaining customer satisfaction to encourage positive WOM and strengthen customer advocacy. Although religious motivation does not strengthen the satisfaction–WOM relationship, reinforcing Sharia values remains an important strategy for differentiating Islamic banks in an increasingly competitive market.Originality – This study extends the Islamic banking literature by examining the moderating role of religious motivation in the customer satisfaction–WOM relationship, an area that has received limited empirical attention. Unlike previous studies emphasizing customer loyalty and behavioral intention, this study identifies WOM as a distinct and important behavioral outcome in the Islamic banking context.